The Effectiveness of Using Quizizz Media in Improving Students' Arabic Writing Skills at MTs Raudatul Ulum Batu - Zaharo Zaharo; Robby Jundi Lestari; Hasan Saefuloh; Maria Ulfa (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Writing is the most challenging Arabic language skill, because it involves thinking and writing. Many students at MTs Raudatul Ulum struggle with writing skills, and the lack of technology-based media exacerbates this problem. Therefore, the use of technology such as Quizizz is very important to improve students' writing skills. This research aims to assess the effectiveness of Quizizz in improving the writing skills of 26 seventh grade students at MTs Raudatul Ulum Batu. The research design used is a quantitative experiment, with data collection through observation, documentation and questionnaires. Data analysis uses descriptive analysis, regular tests, independent sample tests, and paired sample difference tests. The results of this research show that Quizizz is very effective in improving students' Arabic writing skills. Statistical analysis shows that there is a significant difference in student learning outcomes before and after using Quizizz (p = 0.000, less than 0.05). Based on these findings, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted, thus the statistical results confirm that Quizizz has a positive impact on students' Arabic writing abilities. This research contributes to strategies in learning Arabic to overcome students' difficulties in mastering Arabic writing skills.